Analyzing the Interaction of Andrographolide and Neoandrographolide, Diterpenoid Compounds From Andrographis Paniculata (Burm.F) Nees, to Cyclooxygenase-2 Enzyme by Docking Simulation - Jutti Levita; Enade P. Istyastono; As'ari Nawawi; Abdul Mutholib; Iwan J. P. de Esch; Slamet Ibrahim (Institute for Research and Community Services (LPPM) ITB, 2009)
Cyclooxygenase (COX), an enzyme involved in the conversion of arachidonic acid to prostaglandins, exists in two isoforms, which are COX-1 and COX-2. Despite the similarities of COX-1 and COX-2, the two isoforms show subtle differences in amino acid composition at the active sites. Since COX-1 has isoleucine, a bulkier amino acid at position 523 than COX-2's valine, it allows COX-2 to have a larger space in its active site. Andrographolide reduces COX-2 expression induced by PAF and fMLP in HL60/neutrophils. Neoandrographolide inhibits COX-2 expression at the translational level. The purpose of this study is to examine the binding modes of andrographolide and neoandrographolide against COX-1 and COX-2 in terms of hydrogen bonds and docking energy, to understand their antiinflammatory property. The docking simulation indicates that both andrographolide and neoandrographolide are able to be located in the COX-2's binding pocket but not in the COX-1's. It confirms that COX-1's binding pocket is smaller than COX-2's. Based on this study, both andrographolide and neoandrographolide show selective inhibitory property to COX-2. Their selectivity are due to their specific interaction with Arg 513 in the binding pocket of COX-2, which is also shown by SC-558, a COX-2 selective inhibitor.